Biochemistry for dummies - Moore, John T., 1947-; Langley, Richard (Hoboken, NJ : Wiley Pub., 2011)
'This friendly guide presents an easy-to-follow overview of the material covered in a typical college-level biochemistry course'--P. [4] of cover.
Are you baffled by biochemistry? If so here's the good news ? you don't have to stay that way! Biochemistry For Dummies shows you how to get a handle on biochemistry, apply the science, raise your grades, and prepare yourself to ace any standardized test. This friendly, unintimidating guide presents an overview of the material covered in a typical college-level biochemistry course and makes the subject easy to understand and accessible to everyone. From cell ultrastructure and carbohydrates to amino acids, proteins, and supramolecular structure, you'll identify biochemical structures and reactions, and send your grades soaring--
Pt. 1. Setting the stage: basic biochemistry concepts -- Biochemistry : What you need to know and why -- Seems so basic : Water chemistry and pH -- Fun with carbon : Organic chemistry -- Pt. II. The meat of biochemistry: proteins -- Amino acids : The building blocks of protein -- Protein structure and function -- Enzyme kinetics : Getting there faster -- Pt. III. Carbohydrates, lipids, nucleic acids, and more -- What we crave : Carbohydrates -- Lipids and membranes -- Nucleic acids and the code of life -- Vitamins : Both simple and complex -- Hormones : The body's messengers -- Pt. IV. Bioenergetics and pathways -- Life and energy -- ATP : The body's monetary system -- Smelly biochemistry : Nitrogen in biological systems -- Pt. V. Genetics: why we are what we are -- Photocopying DNA -- Transcribe this! RNA transcription -- Translation : Protein synthesis -- Pt. VI. The part of tens -- Ten great applications of biochemistry -- Ten biochemistry careers.
Includes index.
Keywords: Biochemistry